2008
DOI: 10.1016/j.cell.2008.03.036
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Induces Two Distinct Caspase-8 Activation Pathways

Abstract: The inflammatory response of mammalian cells to TNF-alpha can be switched to apoptosis either by cotreatment with a protein synthesis inhibitor, cycloheximide, or Smac mimetic, a small molecule mimic of Smac/Diablo protein. Cycloheximide promotes caspase-8 activation by eliminating endogenous caspase-8 inhibitor, c-FLIP, while Smac mimetic does so by triggering autodegradation of cIAP1 and cIAP2 (cIAP1/2), leading to the release of receptor interacting protein kinase (RIPK1) from the activated TNF receptor com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

60
1,228
4
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,228 publications
(1,302 citation statements)
references
References 42 publications
60
1,228
4
10
Order By: Relevance
“…Indeed, as previously reported, RIP1-independent (TRADDdependent) and RIP1-dependent apoptotic pathways can be activated when cells are stimulated with TNFα and CHX or TNFα and SMs, respectively. 17 We found that NIK +/+ and NIK − / − MEFs equally died following exposure to TNFα/CHX, indicating that the RIP1-independent pro-apoptotic machinery was intact in NIK-deficient cells (Figure 2a Figures S2b-d). We recently showed that the RIP1 kinase inhibitor necrostatin-1 (Nec-1) prevented SM/TNFα-induced caspase activation.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, as previously reported, RIP1-independent (TRADDdependent) and RIP1-dependent apoptotic pathways can be activated when cells are stimulated with TNFα and CHX or TNFα and SMs, respectively. 17 We found that NIK +/+ and NIK − / − MEFs equally died following exposure to TNFα/CHX, indicating that the RIP1-independent pro-apoptotic machinery was intact in NIK-deficient cells (Figure 2a Figures S2b-d). We recently showed that the RIP1 kinase inhibitor necrostatin-1 (Nec-1) prevented SM/TNFα-induced caspase activation.…”
Section: Resultsmentioning
confidence: 79%
“…Caspase-8 is either activated 1 within a TRADD/FADD-containing complex (complex IIa) or in a RIP1/FADD-containing complex (complex IIb). 17,18 The former assembles when cells are deficient in p65 or pretreated with cycloheximide (CHX), whereas the latter forms in the absence of c-IAP1/2, in TAK1 kinase-inhibited conditions or in NEMO-depleted cells. 19,20 In addition, under caspase-repressed conditions RIP1 associates with RIP3 to mediate necroptosis, a form of programmed necrosis that takes place during viral infection or TNF alpha (TNFα)-induced systemic inflammatory response syndrome (SIRS).…”
mentioning
confidence: 99%
“…[43][44][45][46] In this unmodified form, RIP can leave the TNF-R1 complex to associate with Fas-associated death domain (FADD) and procaspase 8 and form death-inducing signalling complex also known as Complex II. 27,43,[47][48][49] The use of IAP antagonists or loss of cIAP proteins generates a similar ripoptosome complex consisting of RIP1, FADD and caspase 8, with components of this complex being subject to ubiquitination and inactivation by cIAPs. [49][50][51] Complex II and the ripoptosome can promote processing of procaspase 8 to its active form resulting in triggering of the caspase cascade that culminates in cell death by apoptosis.…”
Section: Rip1 and Tnf Signalling: Inflammation Versus Apoptosismentioning
confidence: 99%
“…27,43,[47][48][49] The use of IAP antagonists or loss of cIAP proteins generates a similar ripoptosome complex consisting of RIP1, FADD and caspase 8, with components of this complex being subject to ubiquitination and inactivation by cIAPs. [49][50][51] Complex II and the ripoptosome can promote processing of procaspase 8 to its active form resulting in triggering of the caspase cascade that culminates in cell death by apoptosis. 45 Recently, we have demonstrated that a member of the Pellino E3 ubiquitin ligase family, Pellino3, targets RIP1 and impairs Complex II formation in the TNF signalling pathway to suppress cell apoptosis.…”
Section: Rip1 and Tnf Signalling: Inflammation Versus Apoptosismentioning
confidence: 99%
“…Similarly, cellular inhibitors of apoptosis (cIAPs) positively and negatively regulate inflammasome activation and caspase 1 processing, 12 and also compromises caspase 8 activation at the death receptor DISC. 13 Thus, via ubiquitination of specific signaling components cIAPs may shift the inflammasome response towards inflammation and pyroptosis, or immunologically silent apoptosis. 14 At the end, it remains to be asked why nature has invented a system that allows simultaneous induction of cell death by pyroptosis and associated inflammation, and apoptosis.…”
mentioning
confidence: 99%